A new species of Monodiamesa Kieffer, 1922 from southern Chile (Diptera: Chironomidae: Prodiamesinae) - Andersen, T.
(Es, En)
Ilus., 15 ref.
Keywords: DIPTERA; CHIRONOMIDAE; IDENTIFICACION; ESPECIES NUEVAS; REGISTRO; CHILE; REVISTA CHILENA DE ENTOMOLOGIA